2017
DOI: 10.1177/2047487316688982
|View full text |Cite
|
Sign up to set email alerts
|

Association between patient activity and long-term cardiac death in patients with implantable cardioverter-defibrillators and cardiac resynchronization therapy defibrillators

Abstract: Background Patient activity (PA) has been demonstrated to predict all-cause mortality. However, the association between PA and cardiac death is unclear. Aims The aims of this study were to determine whether PA can predict cardiac death and what is the cut-off of PA to discriminate cardiac death, as well as the mechanism underlying the relationship between PA and survival in patients with home monitoring. Methods This study retrospectively analysed clinical and implantable cardioverter-defibrillator/cardiac res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 18 publications
1
34
1
Order By: Relevance
“…One multicenter retrospective cohort study of patients, however, found the association between “low D‐PA” (<30 min/d) and HF hospitalization to be nonsignificant in both unadjusted and adjusted models . This discrepant finding may reflect the different activity threshold used to define “low activity” in this study, which was considerably lower than the thresholds used in the other studies (<60–<113 min/d) . These data highlight an important shortcoming of data‐driven categorization of continuous variables and support the need for evidence‐based clinical thresholds for D‐PA.…”
Section: Resultscontrasting
confidence: 70%
See 4 more Smart Citations
“…One multicenter retrospective cohort study of patients, however, found the association between “low D‐PA” (<30 min/d) and HF hospitalization to be nonsignificant in both unadjusted and adjusted models . This discrepant finding may reflect the different activity threshold used to define “low activity” in this study, which was considerably lower than the thresholds used in the other studies (<60–<113 min/d) . These data highlight an important shortcoming of data‐driven categorization of continuous variables and support the need for evidence‐based clinical thresholds for D‐PA.…”
Section: Resultscontrasting
confidence: 70%
“…One study of patients with pacemakers and preserved left ventricular function showed that all‐cause mortality increased as daily D‐PA decreased and that patients with lower D‐PA at baseline (<1 hour of activity per day) had a 7.4‐fold elevated mortality risk at follow‐up, compared with those who were more active (>3 h/d). Early activity (average activity over the first month after implantation) was also found to be inversely associated with all‐cause mortality and cardiac morality . Although these data are suggestive, they are observational, and thus D‐PA may have served as a marker for unmeasured factors contributing to mortality risk.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations